2007
DOI: 10.1007/s11632-007-0046-7
|View full text |Cite
|
Sign up to set email alerts
|

Research advances in allelopathy of Quercus L.

Abstract: The term allelopathy refers to biochemical interaction between all types of plants including microorganisms through production of chemical compounds that escape into the environment and exist widely in Quercus L. The development of investigations into types of allelochemicals, their compounding and spreading pathways, as well as expression of allelopathy in Quercus L. are reviewed in this paper. We have closely and systematically emphasized the functional mechanisms of allelopathy in forest plants for our next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
9
1
Order By: Relevance
“…By contrast, in the present study, moor grass biomass was not significantly affected by Quercus root exudates. This is at variance with some studies reporting an allelopathic effect of Quercus sp from different regions on understorey species (Li et al, 2007). Callaway et al (1991) identified an allelopathic property of adult Quercus root exudates that inhibited understorey productivity in woodlands.…”
Section: Root Exudates Of Oak Favour Its Own Growth But Exudates Of Molinia Inhibit Its Own Growthcontrasting
confidence: 61%
“…By contrast, in the present study, moor grass biomass was not significantly affected by Quercus root exudates. This is at variance with some studies reporting an allelopathic effect of Quercus sp from different regions on understorey species (Li et al, 2007). Callaway et al (1991) identified an allelopathic property of adult Quercus root exudates that inhibited understorey productivity in woodlands.…”
Section: Root Exudates Of Oak Favour Its Own Growth But Exudates Of Molinia Inhibit Its Own Growthcontrasting
confidence: 61%
“…However, such inhibitory effects could be caused by allelochemicals interfering with physiological and biochemical processes in target species (Weir et al 2004;Gniazdowska and Bogatek 2005;Blanco 2007). Indeed, it has been reported that the inhibition of germination may be the consequence of the inhibition of water uptake, enzyme activity and increased abscisic acid content (Guang-de et al 2007;Turk and Tawaha 2003). Two years earlier, Muscolo et al (2001) reported that the inhibition of seed germination in Pinus laricio was attributed to a disruption of the activity of metabolic enzymes that are involved in glycolysis (first step in dark respiration) and the oxidative pentose phosphate pathway (OPPP).…”
Section: Resultsmentioning
confidence: 99%
“…However, acorns that dropped beneath mother oaks did not survive well due to the allelopathy (Li et al. 2007) and the Janzen–Connell effect (Janzen 1970; Connell 1971; Liu et al. 2012; Wallraf & Wagner 2019).…”
Section: Discussionmentioning
confidence: 99%